Mechanical behavior of polyethylene terephthalate (PET) and geotechnical applications - Eduardo Botero Jaramillo; Liliana Muñoz; Alexandra Ossa; Miguel P. Romo (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
During  the  last  years  solid  waste  disposal  has  increasing  significantly, causing health and environmental problems. In order to study an alternative to mitigate these problems, the re-use of polyethylene- terephthalate bottles as a replacement of conventional lightweight materials used on the leveling or filling of soils is investigated.For  this  purpose,  a  mechanical  characterization  of  the  PET  most  popular  bottles  on  the  market  was  carried  out.  Laboratory  test  results  indicate  that  PET bottles exhibit compression resistances, which suggest that this material can be used on the construction of lightweight structures.